NASKAH AL-JAWAHIR AL-KHAMSAH SEBAGAI SUMBER RUJUKAN AJARAN TAREKAT SYATTARIYAH DAN PERSEBARAN SALINANNYA - Muhamad Shoheh (Al Qalam, 2018)
This paper discusses the context of the written text of alJawahir al-khamsah by Syaikh al-MuhammadAl-Gaus al-Hindi and its relation to a number of other texts which become the source of reference teaching institutes Syattariyah. It also discussed the important position of al-Jawahir al-khamsah text for the followers of the Syattariyah congregation, as well as a general overview of the distribution of copies either in India, Haramayn, and the archipelago. Kitab Al-Jawahir Al-khamsah is a practical book for the followers of Syattariyah congregation the most popular, because it was written based on the author's experience of spiritual exercises tauGt by the teacher, Syaikh Zuhur al-Haji Huduri, for more than 13 years at the top of Mount Janar (Cunar), North India. Kitab al-Jawahir al-Khamsah is a complement of the book of reference Lata'if al-Gaibiyyah and Risalah Syatariyah. So called, because the book of al-Jawahir al-Khamsah contains concepts the idea of founders Syattariyah (Syaikh 'Abdullah al-Syattar} and his followers (Syaikh Baha'uddin), but in a more practical form. Syaikh al-Mufammad Al-Gaus called it asa ''jewel" (الجوهر ) consisting of 'compassion' ('ibadah) and the procedures, zuhd and the procedures, and the procedures creations of prayer, remembrance and the procedures, as well as about the legacy of truth and 'a 'mal al-muhaqqiqin (deeds experts nature) and how to take it. Until now discovered at least five copies of the manuscript al-Jawahir al-Khamsah scattered in various regions, such as India, the Archipelago, Leiden (Netherlands), Saudi Arabia, and Tunisia as one of the countries in the area of North Africa. The manuscript consecutively numbered and each code: 189 خ- ج ; A 37; A 42; Cod.Or. 7201; and A-MSS-07150. This limited findings certainly do not rule out the existence of a copy of the manuscript al-Jawahir al-Khamsah other in other countries, particularly in India and Pakistan as well as Asean countries other than Indonesia.